A Book Interaction Scheme to Enhance Children’s Reading Experiences and Preferences - Zhang, Mingming; Hou, Guanhua; Chen, Yeh-Cheng; Zhang, Tao; Yang, Jie (Frontiers in Psychology, 2020)
The interaction between children and books is an essential part of the reading experience. Publishers all over the world are working to cultivate reading habits in children and attract attention to traditional books. Considering the invaluable nature of these early reading experiences. This paper investigated the effects of book interaction design on 5–6 years old children, taking into account reading preferences, measuring reading time, and emotional response to improve their reading experience and potentially design books according to these interactions. The results showed that preschool children (5–6 years old) prefer sensory interaction, and that book interaction design has a significant influence on reading time, affective experience, and subjective ratings. Girls around 5–6 years preferred folding interaction and pop-up interaction in reading. This study summarizes these results in order to provide practical guidelines for book publishers, enabling them to design better books for children.